Path Students During the COVID-19 Pandemic Analysis of Factors Influencing the GPA of UNIMED FMIPA Mathematics - Rosalia Rusline Simanjuntak; Hamidah Nasution (PT FORMOSA CENDEKIA GLOBAL, 2023)
At the lecture level, learning achievement is measured by IPS (Semester Achievement Inkdes). The influencing factors are the long duration of online learning, attendance, network and study time. In this study, path analysis was used which is a particular form of regression analysis in which the independent variables studied not only directly affect the dependent variable but also indirectly. Based on the results of the discussion, the equation model Y=-0.548X_1+0.042X_2-5.66X_3+11.4 is thus the influence of exogenous variables (X), namely the duration of online learning, presence and networking on the endogenous variable (Y), namely the amount of study time per week of 88.58% and 11.42% influenced by other variables outside the path model. Z=-0.005X_1+0.317X_3+0.93Y+44.3. Thus the influence of the exogenous variable (X), which is many (????), namely IPS, is 11.4% and 44.3% is influenced by other variables outside the path model. And the factor that most influences the IPS score is the network because it has the greatest total influence among the other variables, namely 1.742.